Troubleshooting Assistance Services in Community Wireless Networks - P. Kriz; F. Maly (Journal of Computer Networks and Communications)
We have identified new services intended for users and administrators of community wireless networks. Troubleshooting assistance services will assist the users during solution of communication problems, gathering data for expert analysis, informing the user about the state of the network (including outages), and so forth. Network administrators will be provided with a unique tool supporting the network analysis, operation, and development. We have mainly focused on the use cases and prerequirements—the problem of topology discovery.